Corporate image no longer leads to customer satisfaction and loyalty: a Malaysian perspective. Issue 4 (9th July 2018) - Moorthy, Krishna; Chun T'ing, Loh; Ai Na, Seow; Tze Ching, Chew; Yuin Loong, Lee; Sze Xian, Lim; Wei Ling, Teoh
Abstract : Purpose: This paper aims to study the factors that influence customer loyalty toward the internet service providers in Malaysia. The five factors used are corporate image, perceived quality, perceived value, price fairness and promotion. The mediating variable of this study is customer satisfaction, while customer loyalty is the study variable. Design/methodology/approach: The primary data collection has been done by distributing survey questionnaires to 338 internet users in Malaysia. The data collected have been analyzed with SAS software. Findings: The results showed that perceived quality has the strongest influence on customer satisfaction toward internet service providers in Malaysia. However, corporate image has no relationship with customer satisfaction toward internet service providers in Malaysia. Furthermore, customer satisfaction has a significant and positive relationship to customer loyalty toward the internet service providers in Malaysia. Originality/value: European Customer Satisfaction Index has been adopted and combined with price fairness and promotion as a new research model that other researchers may look into it further. This research may also serve as a guide to internet service providers as they may learn about the underlying factors that affect the satisfaction and loyalty of customers and which factor has the strongest impact.